Bone health from infancy to adolescence: a narrative review of nutritional and lifestyle determinants - Moudgil, Khayati; Bangalee, Varsha; Aku, Thelma Mpoku Alalbila; Rekha, Mekkanti Manasa (International Journal of Research in Orthopaedics, 2025)
Lifelong bone health is largely determined by the foundation established during childhood and adolescence, when the skeleton undergoes rapid growth and mineralization. This paper explores the critical influence of early-life factors including nutrition, physical activity, hormonal balance and disease states on the development of peak bone mass, a key predictor of osteoporosis and fracture risk in later years. Emphasis is placed on the roles of calcium and vitamin D, the resurgence of nutritional rickets in both developing and developed regions and the decline in physical activity among youth worldwide. This narrative review integrates findings from global studies to highlight the importance of balanced diets, regular weight-bearing exercise and early screening in vulnerable populations. Ultimately, it underscores the need for a comprehensive public health strategy to promote optimal bone development from infancy through adolescence, ensuring skeletal resilience across the lifespan.